Ambulation capacity, age, immunosuppression, and mechanical ventilation are risk factors of in-hospital death in severe COVID-19: a cohort study (Clinics, 2022)
Importance: Despite ambulation capacity being associated with a decreased level of physical activity and survival may be influenced by the functional capacity, studies have not addressed the association between ambulation capacity and death in patients hospitalized by COVID-19.Objective: To verify the functional, clinical, and sociodemographic risk factors associated with in-hospital death in individuals with severe COVID-19.Methods: It is a cohort retrospective study performed at a large tertiary hospital. Patients 18 years of age or more, of both sexes, hospitalized due to severe COVID-19 were included. Cases with dubious medical records and/or missing essential data were excluded. Patients were classified according to their ambulation capacity before the COVID-19 infection. Information regarding sociodemographic characteristics, in-hospital death, total hospital stays, Intensive Care Unit (ICU) stays, and the necessity of Mechanical Ventilation (MV) were collected from medical records and registered in a RedCap database. Multiple logistic regression analysis was used to identify possible factors associated with the in-hospital death rate.Results: Data from 1110 participants were included in the statistical analysis. The median age of the patients was 57 (46‒66) years, 58.42% (n = 590) were male, and 61.73% (n = 602) were brown or black. The case fatality rate during hospitalization was 36.0% (n = 363). In-hospital death was associated with ambulation capacity; dependent ambulators (OR = 2.3; CI 95% = 1.2–4.4) and non-functional ambulation (OR = 1.9; CI 95% = 1.1–3.3), age [older adults (OR = 3.0; CI 95% = 1.9‒4.), ICU stays (OR = 1.4; CI 95% = 1.2‒1.4), immunosuppression (OR = 5.5 CI 95% = 2.3‒13.5) and mechanical ventilation (OR = 27.5; CI 95% = 12.0–62.9).Conclusion and relevance: Decreased ambulation capacity, age, length of ICU stay, immunosuppression, and mechanical ventilation was associated with a high risk of in-hospital death due to COVID-19.